Intercultural Competence in Fostering Teachers’ Reflection in Understanding Students’ Diversity - Winarti, Oktifani (Faculty of Communications Science, Dr. Soetomo University, 2017)
In recent decades, the development of multicultural competence, or synonymously called intercultural competence (IC), has been developed as a theoretical context in education areas. Teachers’ inner reflection can do more in specific aspect of learning quality by understanding students’ cultural differences through intercultural competence understanding. Adding self-reflection in the process of understanding interaction within different cultures and language will add more self-value in lessen the ethnocentricity. As teachers are having different culture experience, they would share to each other about the differences to another teacher, in which it allows the teachers to reflect from one another. This would subsequently, help teachers to run innerreflection to themselves, to dig more on their own values, that probably added after having cultural-changing experience Keywords: Intercultural competence, teacher, student diversity